Along with the privilege of authorship come important responsibilities - Moher, David (Université d'Ottawa | University of Ottawa, 2014)
Abstract Transparently documenting who and why a person is an author of a clinical trial report, as with any other article, is important since it allows research team members appropriate recognition and also likely helps reduce or avoid problems such as ghost authorship. Marušić and colleagues have previously proposed a five-step framework for attributing authorship of pharmaceutical company-sponsored clinical trials. The process is short, easily implemented, and can be used in addition to the authorship guidance provided by the International Committee of Medical Journal Editors. For the framework to gain optimal traction it is important that a strong implementation plan is developed and carried out across a broad spectrum of stakeholders. Authorship brings with it important responsibilities; authors must ensure that articles baring their names must be fit for purpose. This will help guarantee an increased value for published reports of clinical trials. Please see related article: http://www.biomedcentral.com/1741-7015/12/197